Comparative study of archaeological contexts of silver hoards c. 800-1050 in Northern and Central Europe - Gruszczynski, J (2016)
The dissertation deals with the archaeological context of Baltic-zone silver hoards deposited in the Viking Age. Its main objective is to investigate the hoards and the context of their deposition to determine how hundreds of thousands of silver artefacts, mainly Oriental dirhams, arrived in Northern Europe, why they were put in the ground and never retrieved. The review of the published sources on hoards was undertaken in three case studies: Gotland, Pomerania and Svealand. The data on hoards, archaeological sites, geology and topography was collected in geodatabases, and analysed in detail by applying descriptive and advanced statistical methods: regression modelling and GIS-based spatial analysis. The results were presented in the historical context depicted in contemporary literary sources. Hoard deposition was most pronounced near sites which afforded conditions suitable for mercantile exchange and facilitated the flow of silver: the network of emporia, regional trade hubs, local power centres, and harbours, generally situated near major communication routes and within populated areas. However, exchange networks needn’t have been strictly hierarchical, and emporium-scale sites were not indispensable for a fair share of silver influx, and trade, to occur. Chronological changes in hoard distributions, their composition and fragmentation of objects indicate how these networks operated and meshed with economic and political conditions in c. 900 and c. 980. A method, which uses the information about the presence/absence of a container, crossreferenced with the weight of silver, was devised to provide an indication as to whether particular hoards were deposited with the aim of retrieval – as savings accessed periodically, or for protection in the face of danger – or whether they were meant to be permanent ritual or symbolic offerings. Ritual behaviour took a variety of forms, but the most widespread were the depositions in recently occupied land in marginal soils, where they were aimed at forging a personal bond between the land and the owner.